Regiões culturais: a construção de identidades culturais no Rio Grande do Sul e sua manifestação na paisagem gaúcha - Brum Neto, Helena (2007)
The organization of the space analyzed by a cultural view allows us to visualize a range of material and immaterial aspects that go by the time and they materialize in the space, as a cultural legacy, that shows itself through the descent. In that perspective, this research is centered in the analysis of the construction of cultural identities in Rio Grande do Sul and its manifestation in the gaúcho landscape, pointing out the main existent cultural areas now in the State. For so, it was started from the theoretical rescue which based the guiding concepts of the research, centered in the culture conception, as a concept-key for the Cultural Geography. It was also approached subjects as identity, codes, migrations, landscape and cultural area. The rescue of the occupation processes and colonization that populated the territory turned into an essential phase for the understanding of its current social cultural structuring, allowing us to verify the transformations happened in the space and expressed in the landscape through the different ethnic groups by the insert of new cultural codes. Our main goal was to regionalize the State by cultural criteria, in other words, to establish space cuttings in agreement with the predominant ethnic group, having as base the municipal limits. For so, it was created a database concerning the main ethnic groups, formers of the 496 municipal districts that compose the State. With this information, it was made the insert in the Arc View GIS 3.1a software, which made that proposal of cultural regionalization operational. As a result four space cuttings were individualized: the cultural area 1 (of native origin, Portuguese, Spaniard, African and Açoriana), the cultural area 2 (German), the cultural area 3 (Italian) and the cultural area 4 (mixed). Besides the cultural areas, cultural islands were individualized in the State, by the presence of a predominant ethnic group, but that doesn't constitute a region due to the "ethnic isolation" of its surroundings, composed by other cultures. Delineated the regional cuttings, it was made the analysis of the cultural areas, in agreement with the expressiveness and the manifestation of the symbolic system that accompanies each society in its relation with the space and people. In agreement with the work proposal, this research was structured in five chapters, plus the introduction and of the final considerations: the chapter 1 refers to the theoretical rescue; in the chapter 2 the methodology is emphasized; the chapter 3 approaches the pertinent subjects the first phase of settlement of the State; the chapter 4 analyzes the colonization process, with emphasis for the immigration German, Italian and mixed; the chapter 5 identifies the cultural areas that compose Rio Grande do Sul now. It is pointed out that, the principal cultural codes identification that emanate of each social group made the analysis of the contribution of each ethnic group for the construction of the gaúcho culture possible. In that context, it can be considered the complexity of the ethnic-cultural composition of the gaúcho territory, originating from the population flows, which were inserted by processes controlled by specific politics of incentive to the settlement and the colonization. Such situation originated portions of the space endowed with meanings that, in turn form a cultural plurality, in other words, nowadays, the State is constituted in a ethnic-cultural mosaic, composed by diversified ethnic groups, at the same time that are recognized as essentially gaúchos .